STRUKTUR NARASI CERITA RAKYAT DALAM KUMPULAN HIKAYAT SA-IJAAN DAN IKAN TODAK - Sri Juniati (STKIP Paris Barantai, 2020)
The purpose of this research is to describe the narrative structure of the folklore in the book Hikayat Saijaan and Ikan Todak and to describe the cultural values ​​contained in the saga Saijaan and Ikan Todak books. This research method is discourse analysis. Meanwhile, this type of research is literature research, namely research that is carried out only based on written work, including research both already and unpublished. This type of qualitative research with literature study through the steps of collecting and analyzing data with data reduction techniques, data presentation, data grouping, and drawing conclusions about the structure of folklore and cultural values ​​in the books Hikayat Saijaan and Ikan Todak. The results showed the structure of the story narrative in the book Hikayat Sa-Ijaan and Ikan Todak, namely the introduction (initial), development (middle) and completion (end). Meanwhile, the cultural values ​​in the book Hikayat Sa-Ijaan and Ikan Todak are character related to God, man with man, man with the universe, man with other creatures, and man with himself. This is evidenced by reading the book Hikayat Saijaan and Ikan Todak repeatedly and grouping the data according to the theory used. Keywords: narrative structure, Hikayat Sa-Ijaan and Todak Fish